Health status and morphometrics of Galápagos magnificent frigatebirds (Fregata magnificens magnificens) determined by hematology, biochemistry, blood gas, and physical examination - Guzmán,Kimberly E.; Deresienski,Diane; Muñoz-Pérez,Juan Pablo; Passingham,Ronald K.; Skehel,Alice; Ulloa,Catalina; Regalado,Cristina; Lewbart,Gregory A.; Valle,Carlos A. (PeerJ, 2024)
The magnificent frigatebird (Fregata magnificens; MFB) is a widely distributed seabird. It has breeding areas in the tropical Atlantic Ocean and the Pacific Ocean (extending along Central America up to Baja California) (Schreiber & Burger, 2001). The Fregata magnificens magnificens (MFB-Gal) subspecies is native to the Galápagos Islands. This is the first-time hematology and blood chemistry parameters have been published for the F. m. magnificens (MFB-Gal) from the Galápagos Islands. Analysis was run on blood samples drawn from n = 16 adult MFB-Gal captured by hand at their nests at North Seymour and Daphne Major Islands in the Galápagos Islands (n = 10 MFB-Gal in June 2017 and n = 6 MFB-Gal in July 2022). There were ten female birds and six male birds in total. A portable blood analyzer (iSTAT) was used to obtain near immediate field results for total carbon dioxide (TCO2), hematocrit (Hct), hemoglobin (Hb), sodium (Na), potassium (K), chloride (Cl), ionized calcium (iCa), total protein (TP), anion gap and glucose. Blood lactate was measured using a portable Lactate Plus™ analyzer. Average heart rate, respiratory rate, body weight, body temperature, biochemistry and hematology parameters were comparable to healthy individuals of other Fregatidae of the same species (magnificent frigatebird subspecies from Brazil, Fregata magnificens, likely F. m. rothschildi) or similar species (great frigatebird, Fregata minor, from the Galápagos Islands). There were some statistically significant differences between the males and females F. m. magnificens (MFB-Gal) in the Galápagos, including bill depth, bill width, wing length, weight, and chloride blood value. The reported results provide baseline data that can be used for comparisons among populations and in detecting changes in health status among Galápagos magnificent frigatebirds and other populations of magnificent frigatebirds.
Keywords: Biochemistry; Fregata magnificens; Magnificent frigatebird; Galápagos Islands; Hematology; Health status; Physical examination; Blood gas